2013
DOI: 10.1007/s11010-013-1882-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-92b suppresses nonsmall cell lung cancer cells growth and motility by targeting RECK

Abstract: microRNAs play critical roles in the progression and metastasis of nonsmall cell lung cancer (NSCLC). miR-92b acts as an oncogene in some malignancies; however, its role in NSCLC remains poorly understood. Here, we found that miR-92b was significantly increased in human NSCLC tissues and cell lines. Inhibition of miR-92b remarkably suppressed cell proliferation, migration, and invasion of NSCLC cells. Reversion-inducing-cysteine-rich protein with kazal motifs (RECK) was identified to be a target of miR-92b. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…The possible regulatory mechanism of miR-21 can be showed in Fig. 9 [28], [29], [30], [31], [49], [50]. Furthermore, our data further underline the pivotal roles played by miR-21, provide new insight into the progression of squamous cell lung carcinoma, and also suggest that miR-21 may have potential diagnostic and therapeutic value for squamous cell lung carcinoma around the world.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The possible regulatory mechanism of miR-21 can be showed in Fig. 9 [28], [29], [30], [31], [49], [50]. Furthermore, our data further underline the pivotal roles played by miR-21, provide new insight into the progression of squamous cell lung carcinoma, and also suggest that miR-21 may have potential diagnostic and therapeutic value for squamous cell lung carcinoma around the world.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, several reports have demonstrated that PTEN is involved in cell apoptosis in human hepatocellular carcinoma cells [26] and also involved in cell proliferation, migration, and invasion in gastric cancer [27]. RECK is thought to be a tumor invasion and metastasis suppressor gene [28], and was also found to inhibit tumor cell growth and motility in both lung and bladder cancer [29], [30]. Bcl-2 is an oncogene and also a direct participant in the tumor cell apoptosis pathway [31].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-92b directly targets PTEN, promotes cell growth and induces cisplatin chemosensitivity in non-small cell lung cancer (NSCLC) cells (21). Inhibition of miR-92b suppresses NSCLC cell growth and motility by targeting RECK (22). Additionally, miR-92b functions as a potential oncogene in glioblastomas by targeting SMAD3 (23).…”
Section: Discussionmentioning
confidence: 99%
“…19, 20 In addition, acting as either tumor suppressors or oncogenes, miRNAs are involved in several aspects of cancer biology including cell proliferation, apoptosis, migration and invasion. 21, 22 In this study, we focused on miR-152 that belongs to the miR-148/152 family that includes miR-148a, miR-148b and miR-152. Many studies have revealed that members of the miR-148/152 family potentially act as oncogenes and tumor suppressors in different cancers.…”
Section: Discussionmentioning
confidence: 99%